Management of an Extremely Low Birth Weight Infant with Bilateral Renal Obstruction Caused by Candida albicans Fungus Balls - Fabian Brüning; Axel Hegele; Günter Klaus; Rolf F. Maier; Rainer Hofmann (Case Reports in Urology)
We report an extremely low birth weight infant with anuria caused by bilateral Candida albicans fungus balls it was treated with a combination of antifungal therapy, irrigation and pyelotomy. This lead to a recovery of renal function, after a follow-up of 77 month no more Candida was cultured from urine.